Optimum Tuning of a Gyroscopic Vibration Absorber Using Coupled Gyroscopes for Vibration Control of a Vertical Cantilever Beam - F. Ünker; O. Çuvalcı (Shock and Vibration)
This paper deals with the investigation of optimum values of the stiffness and damping which connect two gyroscopic systems formed by two rotors mounted in gimbal assuming negligible masses for the spring, damper, and gimbal support. These coupled gyroscopes use two gyroscopic flywheels, spinning in opposing directions to have reverse precessions to eliminate the forces due to the torque existing in the torsional spring and the damper between gyroscopes. The system is mounted on a vertical cantilever with the purpose of studying the horizontal and vertical vibrations. The equation of motion of the compound system (gyro-beam system) is introduced and solved to find the response measured on the primary system. This is fundamental to design, in some way, the dynamic absorber or neutralizer. On the other hand, the effect of the angular velocities of the gyroscopes are studied, and it is shown that the angular velocity (spin velocity) of a gyroscope has a significant effect on the behavior of the dynamic motion. Correctness of the analytical results is verified by numerical simulations. The comparison with the results from the derivation of the corresponding frequency equations shows that the optimized stiffness and damping values are very accurate.